2015
DOI: 10.7314/apjcp.2015.16.4.1609
|View full text |Cite
|
Sign up to set email alerts
|

8-year Analysis of the Prevalence of Lymph Nodes Metastasis, Oncologic and Pregnancy Outcomes in Apparent Early-Stage Malignant Ovarian Germ Cell Tumors

Abstract: At 26.1 months of median follow-up time (range 1.9-88.5 months), 9 patients retained fertility functions, with uneventful pregnancies in 3 of these. Only one patient (2.6%) had progression of disease at 4.9 months after surgery. The 5-year survival rate was 97.4%. Conclusion: As the rate of pelvic or para-aortic node metastasis in MOGCT is considerable, lymphadenectomy should be incorporated in surgical staging procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, retroperitoneal metastatic lymph nodes become a difficult problem to treat [22][23][24][25]. These lymph nodes can contribute to metastatic spread, thereby affecting the long-term survival of patients [4,5,[26][27][28][29][30]. 125 I brachytherapy, with a higher local concentration of radiotherapy, is particularly well suited for the treatment of retroperitoneal metastasis [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…However, retroperitoneal metastatic lymph nodes become a difficult problem to treat [22][23][24][25]. These lymph nodes can contribute to metastatic spread, thereby affecting the long-term survival of patients [4,5,[26][27][28][29][30]. 125 I brachytherapy, with a higher local concentration of radiotherapy, is particularly well suited for the treatment of retroperitoneal metastasis [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…However, minimal invasive techniques are characterized by increased operating times, increased cost, but also less postoperative pain, fewer adverse events of surgery, and a shorter length of stay in hospital (23, 24). Moreover, Chatchotikawong et al (25) showed in an eight-year analysis that bilateral pelvic and paraaortic lymphadenectomy could offer information regarding disease extension and prognosis, elimination of some microscopic tumors, and clarify the further treatment options postoperatively. As Brown et al (26) mentioned the lack of full surgical staging could lead to limited tissue evaluation and inappropriate over- or under-treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…3 Lymph node metastasis found in 28% of patients with ovarian dysgerminoma and was an independent predictor of poor survival. 4 On germinal ovarian cancer, dysgerminoma is most frequently relately with nodal metastasis.…”
Section: Introductionmentioning
confidence: 99%